Use of Hand Outs in the form of Illustrated Stories to Increase Student Learning Motivation - Yeni Oktasari (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine whether there is an increase in the chemistry learning motivation of class X3 students at Public High School 11 South Sumatra, through the use of handouts in the form of picture stories. Methodology: The instruments used in this research are observation and documentation. Observations are carried out to determine the development of teachers and students in the ongoing learning process. Meanwhile, documentation is carried out to obtain school data, teacher data and also student data. Main Findings: Based on the results of data analysis, the percentage of student motivation before action was 49.4%, cycle I 53.8%, cycle II 60.9%, and cycle III 76.4%, which increased with each meeting, so it can It was concluded that the use of handouts in the form of illustrated stories could increase students' learning motivation. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of using handouts in the form of illustrated stories to increase students' learning motivation on the subject of chemical bonds.